Transformation of Religious Moderation Values through Digital Practices in the Character Building of Generation Z Teacher Candidates - Hilhamsyah; Hartanto, Dody; Saputra, Wahyu Nanda Eka; Alfianti, Nadila; Hanipah, Mia; Alimah, Shofi Roudhotul (Journal of Pedagogy and Education Science, 2025)
The transformation of religious moderation values in education depends on conventional approaches and requires effective utilization of digital media, especially in shaping the character of Generation Z teacher candidates. This study aims to reflect on the understanding, experiences, and strategies of Generation Z teacher candidates in internalizing and spreading the values of religious moderation through digital practices amid the disruption era. Using a qualitative approach, data were collected through in-depth interviews based on open-ended instruments covering conceptual, pedagogical, and digital aspects. The results showed that Generation Z teacher candidates are highly aware of the importance of moderate attitudes in religion, especially in the context of the teaching profession as an agent of tolerance and peace. They actively utilize digital platforms such as social media and short videos to convey inclusive religious messages. However, they also face challenges such as polarization of opinions, negative responses, and a lack of curriculum and training that integrates digital competencies with moderation values. This research recommends strengthening university curricula by integrating religious moderation-based character education with developing contextualized and applicable digital competencies. Technology, in this case, plays a strategic role in shaping the character of future teachers who are inclusive, adaptive, and moderate.